PEMANFAATAN KULIT MANGGIS (Garcinia mangostana L) SEBAGAI FORMULASI TABLET ANTI KANKER YANG PRAKTIS DAN EKONOMIS - Shalahuddin Al Madury; Farida Fakhrunnisa; Azizah Amin (Universitas Islam Indonesia, 2013)
Based on data from the World Health Organization (WHO 2010) deadly disease cancer is number two in the world after heart disease. Therefore, there is need for intensive treatment to overcome these health problems, as proclaimed in the draft long-term development of health of the Republic of Indonesia. One of the plants can be used as an anticancer is mangosteen, Garcinia mangostana L. This plant contains a compound-mangostin xanthone especially play a role in cancer treatment with antioxidants that work crate scavenge free radicals so that a non-radical compounds. Required best alternative in tablet dosage that use more practical and economical as the innovation of the preparation syrups tend to be more complicated and expensive. The method used in this study using the literature method. From the discussion carried out could be concluded that mangosteen peel extract (Garcinia mangostana L) is effective for the treatment of cancer with good stability and a practical and economical, so is very potential to be accepted by society.